2011
DOI: 10.1038/pj.2011.109
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ethylene–styrene copolymer containing syndiotactic polystyrene sequence by trivalent titanium catalyst

Abstract: We describe the synthesis of a styrene-ethylene copolymer using a trivalent titanium-based polymerization catalyst system, tris(acetylacetonate)titanium (Ti(acac) 3 ), combined with triisobutylaluminum-modified methylaluminoxane. Gel-permeation chromatography measurement revealed that copolymerization using the above-mentioned catalyst system yielded a mixture of two different polymers. 13 C nuclear magnetic resonance (NMR) analysis of the Soxhlet-extracted fractions indicated that the insoluble part contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The key to this achievement is living polyinsertion, which can be obtained even with traditional catalysts by working at a low temperature. A similar result was reported by Chu et al by copolymerizing ethylene and styrene at 50 °C to obtain block copolymer with syndiotactic styrene sequences and short polyethylene segments, while other researchers succeeded in the synthesis of ethylene-styrene copolymers with syndiotactic styrene blocks and minor polyethylene segments with different catalysts [13,25,26].…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…The key to this achievement is living polyinsertion, which can be obtained even with traditional catalysts by working at a low temperature. A similar result was reported by Chu et al by copolymerizing ethylene and styrene at 50 °C to obtain block copolymer with syndiotactic styrene sequences and short polyethylene segments, while other researchers succeeded in the synthesis of ethylene-styrene copolymers with syndiotactic styrene blocks and minor polyethylene segments with different catalysts [13,25,26].…”
Section: Introductionsupporting
confidence: 74%
“…The diagnostic signals for isolated styrene units (E-S-E; δ = 44.3, 35.0 and 25.7 ppm) [33,37] or isolated ethylene units (S-E-S; δ = 41.6, 35.5 and 25.1 ppm), as well as those for alternating styrene-ethylene units (44.3, 34.7, 23.4 ppm) [33,36], were not detected. 1 H NMR chemical shifts of S α and T β signals, for the S-E polymer junction, were identified from 1 H- 1 H COSY and 13 C- 1 H HSQC cross-correlations, evidenced, respectively, in Figures S2 and S3, starting from 13 C NMR signals previously reported [26]. The low molecular weight of the synthesized copolymer also allowed the identification of the NMR signals for the polymer end-groups.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…The origin of this selectivity was not clearly established but the simultaneous presence of both oxo- and pinacolo-bridges in the ligand is suspected by the authors to be part of the answer. Later on, Naga et al reported styrene-ethylene copolymerizations performed using trivalent Ti(acac) 3 18 in combination with TIBAL and MMAO [ 34 ]. The syndiotacticity level was also not quantified and activities of the catalytic system were quite low.…”
Section: Copolymerization With α-Olefinsmentioning
confidence: 99%